Interpretation of ground-based magnetic and gravity data for the delineation of potential gold mineralization zones in Subenso, Ghana - Tagoe, Ralph (2016)
A Thesis Submitted to the Department of Physics, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the degree of Master of Philosophy,